Ultrasound evaluation of diaphragm motion in BAG-3 myofibrillar myopathy: A case report. Issue 1 (7th January 2022) - Zhan, Liqiong; Lv, Lan; Chen, Xinyuan; Xu, Xiang; Ni, Jun
Abstract: Rationale: Mutations in Bcl-2-associated athanogene-3 (BAG-3) can cause a rare subtype of myofibrillar myopathies (MFMs), characterized by progressive muscle weakness, cardiomyopathy, and severe respiratory insufficiency in childhood. Little is known about diaphragmatic function in BAG-3 MFM. To our knowledge, this is the first case report of detailed evaluation of diaphragmatic function with ultrasound in BAG-3 MFM. Patient concern: We describe the case of a 15-year-old girl who complained of fever and shortness of breath. Diaphragmatic sonography revealed bilateral diaphragmatic paralysis. Shortness of breath progressed to respiratory failure approximately 3 months later. Diagnosis: A neurologist was consulted and genetic sequencing identified a p.Pro209Leu mutation in BAG-3, yielding diagnosis of BAG-3 MFM leading to bilateral diaphragmatic paralysis. Interventions: Respiratory muscle training and long-term mechanical ventilation. Outcomes: It is quite unfortunate for this patient to have a poor prognosis due to the lack of effective treatment for this genetic disorder. Lessons: This case provides more clinical information for this rare disease which may cause severe diaphragm pathological damage leading to respiratory failure in BAG3 MFM and a future study with a systematic evaluation of a greater number of patients will be necessary to characterize this population.